A new dataset of province- and prefecture-level human development index in China - Pu Gong; Siyao Zhu; Meng Jiang; Bing Zhu; Yongheng Yang (Scientific Data)
Abstract The Human Development Index (HDI) is widely recognized as a key measure for assessing progress in health, education, and income. China’s remarkable advances in human development, coupled with pronounced internal disparities, present a unique context for examining regional development trajectories. Existing HDI datasets, however, often focus on national or provincial scales, leaving finer details at the prefecture level underexplored. Here we introduce the Chinese Human Development Index (CHDI) dataset for the period 2010–2020, which extends the HDI framework to a more granular spatial scale. It encompasses the CHDI values, the three underlying dimension indices (health, education, and income), and the four indicators required to construct them: life expectancy at birth, mean years of schooling, expected years of schooling, and gross national income per capita. These indicators were compiled from population censuses, official development plans, and other authoritative statistical sources. The dataset’s fine-grained resolution and methodological rigor ensure both temporal and spatial comparability, providing a robust empirical foundation for analyzing evolving patterns, policy mechanisms, and regional divergences in China’s human development.